2016
DOI: 10.1007/s13555-016-0093-x
|View full text |Cite|
|
Sign up to set email alerts
|

Amorolfine 5% Nail Lacquer Exhibits Potent Antifungal Activity Compared to Three Acid-Based Devices Indicated for the Treatment of Onychomycosis: An In Vitro Nail Penetration Assay

Abstract: IntroductionOnychomycosis is the most common infectious disease involving nails. The aim of this study was to evaluate the antifungal activity of amorolfine 5% nail lacquer and three different acid-based medical devices indicated in the treatment of onychomycosis using an in vitro nail penetration assay.MethodsFour products were tested in vitro: (a) amorolfine 5% nail lacquer; (b) ethyl lactate and acetic acid; (c) citric acid and urea; (d) ethyl lactate, glycerin, lactic acid, and citric acid. Test products w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…Both were more effective than fluconazole and bifonazole against dermatophytes as well as slightly more potent against candida than terbinafine after 4 days of incubation and at concentrations of ≥10 μg/ml, although the specific sporicidal mechanism for the different antimycotics is still unknown. In a vitro nail penetration model (Ghannoum, Sevin, & Sarkany, ), it shows that even small amounts of amorolfine alone reaching the nail bed inhibit or kill the pathogens, its use is far more better than three acid‐based devices which turns out the PH cannot be low enough to be fungicidal. And in another in vitro study (Seidl et al, ), amorolfine demonstrated significant sporicidal effectiveness on dormant T. rubrum and C. albicans cells even at the lowest tested concentration of 1μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Both were more effective than fluconazole and bifonazole against dermatophytes as well as slightly more potent against candida than terbinafine after 4 days of incubation and at concentrations of ≥10 μg/ml, although the specific sporicidal mechanism for the different antimycotics is still unknown. In a vitro nail penetration model (Ghannoum, Sevin, & Sarkany, ), it shows that even small amounts of amorolfine alone reaching the nail bed inhibit or kill the pathogens, its use is far more better than three acid‐based devices which turns out the PH cannot be low enough to be fungicidal. And in another in vitro study (Seidl et al, ), amorolfine demonstrated significant sporicidal effectiveness on dormant T. rubrum and C. albicans cells even at the lowest tested concentration of 1μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The agar diffusion assay was developed to determine the antifungal activity, measured as ZOI, of amorolfine 5% NL (a microtiter plate assay could not be used due to the opacity of the test agents). The disc‐diffusion method has been widely used to determine the antifungal activity of drugs, and this assay has been described previously . Since there is no standard method for the disc‐diffusion susceptibility testing of dermatophytes, it was necessary to arbitrarily select a ZOI size that could be reproducibly interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…Both tests allowed the development of the fungus in an ideal habitat, but as previously mentioned, when it is intended to evaluate the antifungal activity of some agent in the nail powder, the rigid barrier present in the nail plate that hinders the penetration of the drugs is absent in this case. Another model of dermatophyte infection was that of Ghannoum et al, who used nails removed from fresh human cadavers to check the antifungal potential of a topical solution. This onychomycosis model is easy to reproduce and has been developed with care to ensure that the antifungal effects result from the penetration of the test compound into the nail plate.…”
Section: Alternative Methods That Simulate Fungal Infectionsmentioning
confidence: 99%